Conceptual framework of transparency initiatives (TI) for construction industry of Malaysia - Rumaizah Mohd Nordin,; Zulhabri Ismail,; Noratika Radi @ Radzi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Transparency is one of the practical measures taken to curtail corruption. It is about the sharing of information of government decisions and activities, good record management and access to information. Whereas, integrity provides the basis for transparency and accountability since integrity is referred to as honesty and trustworthiness in the discharge of official duties, serving as antithesis to corruption. Corruption is a fiduciary crime that is believed to slowly penetrate the construction sectors in countries across the globe. Hence, the aim of this paper is to investigate transparency initiatives of construction industry by identifying various strategies to eradicate corruption in the Malaysian construction industry. The methodology used for this research is based on qualitative research technique and the methods are two-folds: (1) preliminary interview, and (2) a well-planned brainstorming workshop. The findings revealed that nine (9) initiatives were taken based on the notion of integrity that can be divided into behavioural and technical issues. These are: Code of Ethics (CoE) for contractors, Integrity program, Bina Integriti journal, Code of Business Ethics for Construction Industry (for SMEs), CIDB reporting and sanctioning structure, Core Values, Legal and Enforcement, Integrity Pacts (IP), and Integrity Role Model. These initiatives are regarded as fundamental efforts in educating and creating awareness to the industry players despite a more drastic strategy could be considered by the construction industry for a more significant results.